Fibrous osteodystrophy in a captive common eland antelope (Taurotragus oryx) - Grandi, Fabrizio [UNESP]; Pessoa, Lourdes M. B.; Filho, Francisco Lúcio; de Araújo, Rochele; Rocha, Rafael M.; del Fava, Cláudia (My University, 2011)
Fibrous osteodystrophy (FO) is a common condition described mainly in domestic species, with only few cases described in wild ones kept in captivity. Herein we report a case of FO in a 2 yr-old female common eland antelope (Taurotragus oryx) maintained in captivity and fed with a horse pelleted ration plus hays. The animal showed a firm bilateral symmetrical enlargement of upper maxillary bones which was submitted to histological evaluation. Microscopic findings were those related to extensive bone resorption and fibroplasia.
Keywords: Antelope; Eland; Fibrous osteodystrophy; Pathology; Taurotragus oryx